Omnichannel Marketing Strategy as Approach Effective in Modern Marketing - Gunawan (Journal of Management, 2022)
Development of digital technology has pushed significant changes in consumer behavior and company marketing strategies. This research aims to analyze the effectiveness of omnichannel marketing strategies as a modern approach in reaching and maintaining consumers. Omnichannel marketing integrates various marketing channels — both online and offline — to create a consistent, personal and integrated customer service experience. The research method used is descriptive qualitative with interview observation to omnichannel implementation on several leading retail brands. Research results show that implementation of omnichannel marketing strategy can effectively increase the quality of interaction between companies and customers. Through observations, interviews and documentation were carried out, it was found that integration of various communication channels — such as social media, websites, physical stores, and customer services — was able to create consistent and satisfying experience for consumers. In addition, the data collected shows that companies that implemented this strategy in a way appropriate experience improved customer loyalty, operational efficiency, as well as positive response to more personal and relevant marketing campaigns.